The factory act 1948: legislation utilized for quality of work life establishment - Pandey, Archana; B K, Jha (Journal of Management and Science, 2013)
Globalization and technical advancement has created a competitive, tougher & stressed professional and personal life for the employees. To reduce their work place tension and to provide the balance in professional and personal life, Quality of work life plays a paramount role. There is no specific enactment with a view to establish Quality of work life at work place. The objective of this research is to examine, review and re-search Indian laws and find acts containing provisions which enforce a standard Quality of work life norms at work place. Also, this study will find out provisions which help employees raise their concerns, grievances and complaints against their employers and legal remedies available to them.